Interests shape how adolescents pay attention: the interaction of motivation and top‐down attentional processes in biasing sensory activations to anticipated events. (26th December 2014) - Banerjee, Snigdha; Frey, Hans‐Peter; Molholm, Sophie; Foxe, John J.
Abstract: The voluntary allocation of attention to environmental inputs is a crucial mechanism of healthy cognitive functioning, and is probably influenced by an observer's level of interest in a stimulus. For example, an individual who is passionate about soccer but bored by botany will obviously be more attentive at a soccer match than an orchid show. The influence of monetary rewards on attention has been examined, but the impact of more common motivating factors (i.e. the level of interest in the materials under observation) remains unclear, especially during development. Here, stimulus sets were designed based on survey measures of the level of interest of adolescent participants in several item classes. High‐density electroencephalography was recorded during a cued spatial attention task in which stimuli of high or low interest were presented in separate blocks. The motivational impact on performance of a spatial attention task was assessed, along with event‐related potential measures of anticipatory top‐down attention. As predicted, performance was improved for the spatial target detection of high interest items. Further, the impact of motivation was observed in parieto‐occipital processes associated with anticipatory top‐down spatial attention. The anticipatory activity over these regions was also increased for high vs. low interest stimuli, irrespective of the direction of spatial attention. The results also showed stronger anticipatory attentional and motivational modulations over the right vs. left parieto‐occipital cortex. These data suggest that motivation enhances top‐down attentional processes, and can independently shape activations in sensory regions in anticipation of events. They also suggest that attentional functions across hemispheres may not fully mature until late adolescence. Abstract : This work examined the influence of level of interest in anticipated stimuli on established ERP indices of spatial attention in adolescents. Results showed significantly greater accuracy in target detection for high versus low interest stimuli, as well as enhanced amplitude in parieto‐occipital processes related to anticipatory spatial attention. This provides a foundation for future work with developmentally disabled populations using level of interest in stimuli as incentive to potentially regulate atypical attentional processes.